Cognitive Engineering of Automated Assembly Processes. Issue 3 (8th May 2012) - Mayer, Marcel Ph.; Odenthal, Barbara; Faber, Marco; Winkelholz, Carsten; Schlick, Christopher M.
Abstract A cognitive control unit (CCU) for automated assembly systems aims to simulate human information processing at a rule‐based level of cognitive control. Focusing on the subtask of monitoring, a cognitive engineering approach for the design of the procedural knowledge base of the CCU is presented and a human‐centered simulation model of assembly processes on the basis of the cognitive architecture SOAR is introduced. The overall objective is to design and develop the system to conform to operators' expectations. To identify human assembly strategies to be included in the CCU, an empirical study with n = 16 participants was conducted and validated by an independent investigation with n = 25 persons. Furthermore, simulation models incorporating certain subsets of production rules were developed and evaluated regarding their goodness of prediction of human assembly behavior. The results show that the rule sets have a significant effect on the predictive power. The highest prediction accuracy was obtained with all identified assembly rules integrated. © 2012 Wiley Periodicals, Inc.